Heidegger's ontology and his contemporaries: Husserl and Cassirer - Andrii Karpenko (Cхід, 2016)
Research into the history of understanding Heidegger's ideas allows to reveal how different thinkers were likely to grasp the specific subjective positions that defined the meaning of philosophizing as a cultural practice posited by modern era of intellectual history. The figure of Heidegger is crucial because it shed light on the more general context of the evolution of philosophizing within the system of scientific knowledge. A clear contrast between scientific rationalism and philosophical thinking, inherent for Heidegger's philosophy, is now hardly perceived within general coordinates of scientific philosophy of the last century, combining directions of phenomenology, Neo-Kantian tradition and positivism.